2023
DOI: 10.1088/1742-6596/2436/1/012031
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of the monomer density profiles of knotted ring polymer chains confined in a slit of two parallel walls with one attractive and another repulsive surface.

Abstract: We have used Molecular Dynamics simulations to obtain the monomer density profiles for real linear and ring polymer chains of 360 monomers length with different topological structures such as simple knots: 31, 61, 91, 10124, complex knots 313151 and twisted knots with n = 10 and n = 20 in a slit geometry of two parallel walls with one attractive and another repulsive surface. We have used Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) software to perform simulations with the Verlet integrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The slit width 𝑧 is on the horizontal axis and is scaled to 1. Narrow slit corresponds to the width of 4.81𝜎 (𝐿 < 2𝑅 𝑔 ) and wide slit corresponds to 19.24𝜎 (𝐿 > 2𝑅 𝑔 ) [28].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The slit width 𝑧 is on the horizontal axis and is scaled to 1. Narrow slit corresponds to the width of 4.81𝜎 (𝐿 < 2𝑅 𝑔 ) and wide slit corresponds to 19.24𝜎 (𝐿 > 2𝑅 𝑔 ) [28].…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that in wide slits, the interaction with the opposite side may be limited, thereby reducing the force exerted on the opposite wall. The density profiles of polymers with varying knot structures are discussed in [28], where it was demonstrated that the wide slit space penetration diminishes with the knot complexity, see figure 3. Conversely, in narrow slits, where the distance is short, both complex and simple polymers can directly influence the opposite slit sides [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation